2023
DOI: 10.3389/fonc.2023.1143122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thromboembolic event, basic coagulation parameters, and associated factors in patients with colorectal cancer: a multicenter study

Abstract: BackgroundPatients with colorectal cancer are at an increased risk of hemostatic disturbances, and recent studies have shown that coagulation disorders could be the first sign of malignancy. Although coagulopathy is a significant cause of cancer-related death and disability, it is usually underestimated, and there has been no recent scientific evidence regarding the exact burden and its specific determinants. Moreover, the public health importance of the risk of coagulopathy among patients with colorectal poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The GO enrichment analysis of the BPs associated with the DEGs revealed that DEGs in the CRC versus CRC liver metastasis dataset were mainly enriched in platelet degranulation, regulation of blood coagulation, acute-phase response, hemostasis regulation, and regulation of coagulation, mainly related to hemostasis and platelet activation. The rst sign of malignancy may be coagulopathy [31] . The coagulation system is hyperactive in patients with malignant tumors due to the procoagulant characteristics of cancer cells, and the activity of the brinolytic system is decreased, which affects various related factors involved in the coagulation process and eventually leads to abnormal coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The GO enrichment analysis of the BPs associated with the DEGs revealed that DEGs in the CRC versus CRC liver metastasis dataset were mainly enriched in platelet degranulation, regulation of blood coagulation, acute-phase response, hemostasis regulation, and regulation of coagulation, mainly related to hemostasis and platelet activation. The rst sign of malignancy may be coagulopathy [31] . The coagulation system is hyperactive in patients with malignant tumors due to the procoagulant characteristics of cancer cells, and the activity of the brinolytic system is decreased, which affects various related factors involved in the coagulation process and eventually leads to abnormal coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) is one of the most common causes of death and morbidity in cancer patients, and CT and immobilization contribute to an increased risk of VTE [76]. The prevalence of coagulopathy, including thrombocytopenia and APTT prolongation, has been shown in patients with CRC [6]. The elevated preoperative and postoperative level of D-dimer (the product of degradation of fibrin by fibrinolysis-mediated plasmin cleavage) and APTT may be risk factors associated with thrombotic events and bleeding, worsening the prognosis of CRC [77][78][79][80].…”
Section: Hemostasis Disordersmentioning
confidence: 99%
“…High heterogeneity, plasticity, and self-renewal help tumor cells avoid immune surveillance, become resistant to chemotherapy (CT) and apoptosis, and spread, creating metastatic niches. A developing tumor has both local and systemic effects on the body, which leads to cachexia, psychoneuroendocrine and immunoinflammatory imbalances, pro-tumoral cytokine production, aberrant myelopoiesis, immunosuppression, chronic inflammation, paraneoplastic syndromes, hemostatic abnormalities, and other disorders [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%